Education Marketing Management Model According To The Paradigm Of Total Quality Management In Education At Madrasah Tsanawiyah Level - Untung, Slamet; Fathudin, Ahmad Ubaedi; Madina, Ghilma; Rokhmah, Asnalia; Kalupae, Abdul Aziz (Intelegensia : Jurnal Pendidikan Islam, 2024)
This research explains the role of the Head of Madrasah Tsanawiyah in the former Pekalongan Residence in implementing educational marketing management based on Total Quality Management in Education, the strategies used in implementing educational marketing management, and the impact on the madrasah regarding the implementation of educational marketing management. The research location is Madrasah Tsananwiyah in the former Pekalongan Residence, Central Java. The primary data is in the form of an educational marketing management model at Madrasah Tsanawiyah. Meanwhile, the secondary data is a theoretical basis obtained through reviewing literature regarding educational marketing management. This research is categorized as field research using a qualitative approach. The data collection techniques include in-depth interviews, observation, documentation and triangulation. The collected data was analyzed using the Miles, Huberman, and Saldana analysis model. The results of the research show that the role of the Head of the Pekalongan Ex-Residency Madrasah Tsanawiyah in implementing educational marketing management according to the TQM in Education perspective includes the managerial role, the role of work program executor, and the role of users of educational marketing facilities and infrastructure. Meanwhile, the strategies used are the Market-Based Management Strategy Model and the Resource-Based Strategy Model. The impacts caused by the implementation of educational marketing management include the fulfillment of planned education quotas, the establishment of cooperation between internal and external parties of the madrasah, and the creation of a positive image of the madrasah in society.